Reliability and Accuracy Test of Digital Anthropometry to Monitor Growth and Development in Children - Kuntuamas, Yulianingsi A; Huriah, Titih (Jurnal Keperawatan Respati Yogyakarta, 2025)
Regular child anthropometry, such as measuring a children height and or length, is a crucial part of pediatric clinical evaluations. Anthropometric measurements of children allow measurement errors caused by weaknesses in measuring instruments, thus affecting the accuracy of measurement results. This review contributes to nursing by providing insights into the reliability and accuracy of digital anthropometric tools, which are essential for ensuring precise growth monitoring in pediatric care. the reliability and accuracy of digital anthropometry tools and contributes to nursing by providing insight into the reliability and accuracy of digital anthropometry tools that are important in monitoring child growth and development. Conventional anthropometric methods, while widely used, face limitations in accuracy due to human error and challenges with measuring children. Digital anthropometry offers a promising alternative with potentially higher precision, ease of use, and adaptability, critical for tracking children’s health metrics like height and weight against growth standards. The study applied the Joanna Briggs Institute methodology, using PRISMA guidelines for literature reviews, and selected seven studies meeting specific inclusion criteria. Studies reviewed technologies such as Auto Anthro, Bland.  Six studies indicated that digital measurements of anthropometry had excellent levels of accuracy and reliability to monitor child growth and development; one study showed less accuracy because it takes more time to test and improve training and ensure the software works as intended. For nurses, using digital anthropometry improves efficiency in clinical practice by enabling rapid and accurate assessments, reducing human error, and increasing the reliability of growth monitoring, thereby enabling early intervention and better health outcomes for children.